Endogenous SIRT6 in platelets negatively regulates platelet activation and thrombosis - Liu, Yanli; Wang, Tao; Zhou, Qilong; Xin, Guang; Niu, Hai; Li, Fan; Wang, Yilan; Li, Shiyi; Dong, Yuman; Zhang, Kun; Feng, Lijuan; Fu, Wei; et al. (Frontiers in Pharmacology, 2023)
Thromboembolism resulting from platelet dysfunction constitutes a significant contributor to the development of cardiovascular disease. Sirtuin 6 (SIRT6), an essential NAD + -dependent enzyme, has been linked to arterial thrombosis when absent in endothelial cells. In the present study, we have confirmed the presence of SIRT6 protein in anucleated platelets. However, the precise regulatory role of platelet endogenous SIRT6 in platelet activation and thrombotic processes has remained uncertain.Herein, we present compelling evidence demonstrating that platelets isolated from SIRT6-knockout mice (SIRT6 -/-) exhibit a notable augmentation in thrombin-induced platelet activation, aggregation, and clot retraction. In contrast, activation of SIRT6 through specific agonist treatment (UBCS039) confers a pronounced protective effect on platelet activation and arterial thrombosis. Moreover, in platelet adoptive transfer experiments between wild-type (WT) and SIRT6 -/-mice, the loss of SIRT6 in platelets significantly prolongs the mean thrombus occlusion time in a FeCl3-induced arterial thrombosis mouse model. Mechanistically, we have identified that SIRT6 deficiency in platelets leads to the enhanced expression and release of proprotein convertase subtilisin/kexin type 9 (PCSK9), subsequently activating the platelet activation-associated mitogen-activated protein kinase (MAPK) signaling pathway. These findings collectively unveil a novel protective role of platelet endogenous SIRT6 in platelet activation and thrombosis. This protective effect is, at least in part, attributed to the inhibition of platelet PCSK9 secretion and MAPK signaling transduction. Our study provides valuable insights into the intricate interplay between SIRT6 and platelet function, shedding light on potential therapeutic avenues for managing thrombotic disorders.